In vitro breeding: application of embryonic stem cells to animal production†. Issue 4 (14th December 2018) - Goszczynski, Daniel E; Cheng, Hao; Demyda-Peyrás, Sebastian; Medrano, Juan F; Wu, Jun; Ross, Pablo J
Abstract: Embryonic stem cells (ESCs) are derived from the inner cell mass of preimplantation blastocysts. For decades, attempts to efficiently derive ESCs in animal livestock species have been unsuccessful, but this goal has recently been achieved in cattle. Together with the recent reconstitution of the germ cell differentiation processes from ESCs in mice, these achievements open new avenues for the development of promising technologies oriented toward improving health, animal production, and the environment. In this article, we present a strategy that will notably accelerate genetic improvement in livestock populations by reducing the generational interval, namely in vitro breeding (IVB). IVB combines genomic selection, a widely used strategy for genetically improving livestock, with ESC derivation and in vitro differentiation of germ cells from pluripotent stem cells. We also review the most recent findings in the fields on which IVB is based. Evidence suggests this strategy will be soon within reach. Abstract : In vitro breeding constitutes a fast and intense selection strategy to genetically improve livestock populations.